The reasons and drivers behind Higher Education ceasing to expand in Russia - Sergey S. Malinovskiy; Ekaterina Yu. Shibanova (Социологический журнал, 2022)
The structural consolidation of the higher education network, a diminishing commercial segment, and an increase in vocational training enrollment over the past decade are all signs that higher education expansion in Russia has come to an end. The aim of this article is to find possible explanations and analyze macro-level factors of this phenomenon from an economic, sociological and political-economic perspective. Based on the statistical and monitoring data, the paper shows that the decrease in enrollment is due to a shortage in higher education programs, limited financial accessibility and shifts in the economic efficiency of educational strategies. Declining participation in higher education seems to be more of a tendency for less affluent and educated families, who are redirecting towards vocational training. A declining number of part-time correspondence programs and university departments, as well as the vertical stratification of the institutional landscape, reinforce the social differentiation of educational expectations and opportunities. The stratification and professionalization of tertiary education are also examined as part of the evolution of the conservative political-economic model in Russia.